A monthly study of the temperatures associated with cloud cover (CM) in Iraq - Al-NAJJAR, Budoor Mohammed Dawood; Al-Waely, Ali Abdul Zahra Kadhem (Al-Adab Journal, 2023)
This research aim to study the relationship of the cloudy cover (moderate CM) for what it contain the (nine) types of moderate clouds and its effect on the superficial temperatures that follow, and connect the relationship between the high and the low boundary for the monthly ranges, compare the time and space contrast between the northern, middle and southern, presence of temperature differences between the temperature is a result of the exposure of the study area to different types of pressure system, heights, lows and what follows of fronts and several air blocs and the effect of height factor above see scale, the astronomical site from width circles, the incidence of the sun ray angle and the length of the day, the clarity of the sky in the summer and winter, the effect of different climatic factors, the presence and absence of the aquatic flats and also to the local climatic circumstances of all terminal, the mankind factors which effect generally on the repetitions of the cloudy cover and the superficial that follow in particular. The study showed that the highest general average monthly was for the eighth type Altocumulus (Ac8) for Basra’s Station which reached (28.7) and the lowest average was for Hilla’s Station (20.6), chronologically the highest average monthly temperature was registered in July, August and September except for Najaf’s Station was in May, and Alsamawah in June.